1982
DOI: 10.1111/j.1365-246x.1982.tb06962.x
|View full text |Cite
|
Sign up to set email alerts
|

On analysis and prediction of tides on the west coast of Great Britain

Abstract: Long-period tidal records from eight ports on the west coast of Great Britain are analysed, using both the harmonic method and the response function. Time series up to 9.5 yr were used so that fine structure of certain regions of high energy in the tidal residual spectrum may be examined. This also assisted in accurate separation of tides from surges. According to the currently accepted formulation of MI, its composition is not compatible with its actual composition in the real tide and, as such, has no useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
41
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 16 publications
11
41
0
Order By: Relevance
“…Many years of experience with Liverpool data (e.g. an unpublished study in the NOC archives of 8 years of Liverpool hourly values by A.T. Doodson in the 1930s) showed that MTL-MSL is about 0.19 feet (6 cm), which is consistent with the 6.5 cm one would calculate using the 110 constituents of Amin (1982). However, if only the shorter set of constituents in Appendix 1 is used, one obtains a smaller value of 4.4 cm.…”
Section: Liverpoolsupporting
confidence: 62%
See 1 more Smart Citation
“…Many years of experience with Liverpool data (e.g. an unpublished study in the NOC archives of 8 years of Liverpool hourly values by A.T. Doodson in the 1930s) showed that MTL-MSL is about 0.19 feet (6 cm), which is consistent with the 6.5 cm one would calculate using the 110 constituents of Amin (1982). However, if only the shorter set of constituents in Appendix 1 is used, one obtains a smaller value of 4.4 cm.…”
Section: Liverpoolsupporting
confidence: 62%
“…A first topic is a demonstration of the contribution of M6, using constants for M2, M4 and M6 from Amin (1982). These three constituents have amplitudes of 312.8, 23.4 and 5.3 cm respectively.…”
Section: Liverpoolmentioning
confidence: 99%
“…First, there is evidence that the amplitude of the ocean tide at Liverpool is slightly larger now than it was in Hutchinson's time (Woodworth, 1999b). Consequently, the subtraction of predictions based on Amin (1982a) will result in surge values biased low. Second, the Amin (1982a) constituents comprise a detailed, but necessarily incomplete, description of the tide, especially with regard to shallow water and seasonal terms.…”
Section: Amxshwmentioning
confidence: 99%
“…(See Graff (1981) for a discussion of the apparent time dependence of extreme level estimates at several UK ports based on short subsets of data). Figure 5 shows four extreme level curves for AMxHW obtained by the GEV method derived from sets 1-3 of real data and from tidal predictions for Liverpool based on the harmonic constituents of Amin (1982a). Some 40 years (i.e.…”
Section: Extreme Level Distributionsmentioning
confidence: 99%
“…As surge heights are related to water depth, they are larger in shallow water than in deeper water (McInnes et al 2011). Shallow water interactions between tides and surges are likely to be responsible for the surge amplitude modification as a result of more energy being lost from tides and surges travelling together, than would be lost if they were travelling separately (Amin, 1982). Horburgh and Wilson (2007) showed that modulation of surge production is due to changes of depth during the tidal cycle.…”
mentioning
confidence: 99%